Academic performance indicators for the hackathon learning approach – The case of the blockchain hackathon - Miličević, Ana; Despotović-Zrakić, Marijana; Stojanović, Danijela; Suvajžić, Marko; Labus, Aleksandra (Journal of innovation & knowledge, 2024)
The subject of this article is an analysis of the hackathon concept as an educational approach and its role in the development of students' knowledge and skills. The goal is to conduct an in-depth examination of the effectiveness and achievements of the hackathon, with special reference to the attitudes of students and teachers involved in this educational methodology. The key emphasis is placed on participants' perception of the possibilities of hackathons providing long-term results and hackathons' impact as an educational format. Through a specific blockchain hackathon jointly organized by the University of Belgrade, Serbia, and the University of Florida, USA, the research examines participants' perspectives and their expectations, experiences, and overall impressions. The research focuses on the readiness of hackathon participants to incorporate new technical skills through this form of learning, knowledge acquisition, attitudes, and motivational drivers. Furthermore, the research examines how participants' views change before and after the event. The paper contains the insights of educators who, relying on their experiences at the hackathon, emphasize the importance of measuring and monitoring the outcome of the hackathon. Their perspectives highlight the motivation for promoting experimental learning methods in academic settings. This comprehensive research sheds light on multiple impacts of hackathon participation, which extend beyond knowledge acquisition to include changes in technological interests, success in specific domains, and the broader implications of hackathons as a transformative learning experience. The research contributes to the ongoing discussion about innovative approaches to learning. It provides a foundation for a better understanding of how hackathons shape attitudes and contribute to long-term outcomes for both students and teachers, establishing a conceptual framework for hackathon-based learning approaches and opportunities to monitor the effects of hackathons.